OPTIMIZING POPULATION ADMINISTRATION THROUGH THE ELECTRONIC IDENTITY CARD (KTP-EL) - Al Azizah, Nafilah Dzakiyah; Agustina, Isna (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the optimization of population administration services through the Electronic Identity Card (KTP-el) system in Jogosatru Village, Sukodono District, Sidoarjo Regency, focusing on improving efficiency and accuracy to support quality public services. Method: A qualitative approach was employed, utilizing in-depth interviews with villagers and village officials. The analysis was guided by the SERVQUAL theory, covering five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Result: The findings reveal that while efforts have been made to enhance KTP-el services, several obstacles persist, including limited facilities, low public understanding, and technical issues in recording and issuance processes. These challenges hinder the full optimization of population administration at the village level. Novelty: This study provides a localized analysis of KTP-el implementation at the village level using the SERVQUAL framework, offering targeted recommendations to improve facilities, strengthen public socialization, and address service quality gaps across all five SERVQUAL dimensions.